Size matters: Measuring the effects of inequality and growth shocks - Sanghamitra Bandyopadhyay; Rui Sun (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Understanding the relationship between income inequality and economic growth is of utmost importance to economists and social scientists. In this paper we use a Bayesian structural vector autoregression approach to estimate the relationship between inequality and growth via growth and inequality shocks for two large economies, China and the USA, for the years 1979- 2018. We find that a growth shock is inequality-increasing, and an inequality shock is growthreducing. We also find, however, that the sizes of the effects of these shocks are very small, accounting for under 2 per cent of the variance for both countries. Finally, we also find that the effects of the shocks dissipate within ten years, suggesting that the effects of these shocks are a short-term phenomenon.
Keywords: C32; C33; D31; D63; 330; inequality; growth; Bayesian structural vector autoregression; China; USA